Net ecosystem fluxes and composition of biogenic volatile organic compounds over a maize field–interaction of meteorology and phenological stages. Issue 11 (1st June 2017) - Wiß, Felix; Ghirardo, Andrea; Schnitzler, Jörg‐Peter; Nendel, Claas; Augustin, Jürgen; Hoffmann, Mathias; Grote, Rüdiger
Abstract: Bioenergy crop production is rapidly expanding in Europe, and the potential emissions of biogenic volatile organic compounds (BVOCs) might change the chemical composition of the atmosphere, influencing in turn air quality and regional climate. The environmental impacts of bioenergy crops on air chemistry are difficult to assess due to a lack of accurate field observations. Therefore, we studied BVOC fluxes from a bioenergy maize field in North‐Eastern Germany throughout the entire reproductive growth stage of the plants. Combining automated large chambers and proton transfer reaction mass spectrometry (PTR‐MS), we successfully measured fluxes of the highly reactive hydrocarbons monoterpenes (MTs) and sesquiterpenes (SQTs), together with several other BVOCs, including alcohols, aldehydes, ketones, benzenoids, and fatty acid derivatives. Emissions of MTs and SQTs were relatively high (17.0% and 3.6% of total mean molar BVOC emission, respectively) compared to methanol emissions (17.6%). Seasonal MT and SQT fluxes were clearly associated with the flowering phase, originating mainly from the flowering tissues as shown in additional laboratory experiments. From the observations of CO2 net ecosystem exchange and evapotranspiration rates, we could exclude heat and drought stress‐induced BVOC emissions. Standard emission factors calculated for all compounds, chemical groups, and growth stages, showed that the temperature dependency of volatile terpenoid fluxes decreased distinctively with proceeding development stage. The results indicate that emissions from large‐scale bioenergy maize fields should be better differentiated and considered in regional estimates of aerosol formation. For the implementation of such relation into biogeochemical modelling, it should be considered that not only seasonal weather development but also phenological growth stages are determining the BVOC patterns and emission potentials. Abstract : We could show that flowering tissues are important additional sources of volatile terpenes. Non‐terpene compounds did not show these phenological and seasonal dependencies but could be explained by instantaneous weather conditions. The application of a new technique that combines large automatic chambers with PTR‐QMS technology, showed the feasibility of measuring BVOC emissions at the field scale continuously over extended time periods. The emission of highly reactive MTs and especially SQTs in significant amounts indicates that maize fields are likely to play an important role in regional aerosol formation and should thus be considered in regional biosphere‐atmosphere feedback analysis, particularly regarding land‐use change scenarios that evaluate bioenergy production impacts.